2013
DOI: 10.1039/c3tc00925d
|View full text |Cite
|
Sign up to set email alerts
|

Erratic magnetic hysteresis of TbPc2 molecular nanomagnets

Abstract: Terbium(iii) bis-phthalocyaninato neutral complex, a robust and evaporable Single Molecule Magnet (SMM) with a record height of the anisotropy barrier, has recently attracted a great interest as an active unit in single molecule electronics, but at the same time its magnetic hysteresis has been found to be strongly affected when the environment is different from the crystalline phase. Here we present a systematic investigation of the magnetization dynamics in different environments, obtained by magnetic diluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
70
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 50 publications
(69 reference statements)
11
70
0
Order By: Relevance
“…On the contrary, our data on TbPc 2 multilayers on MgO reveal that vertical interactions accelerate magnetization relaxation. [ 20,21 ] In summary, we have demonstrated that MgO thin fi lms realize the combination of effi cient protection from electron scattering and weak molecule-surface hybridization to achieve optimal properties of SMMs on electrode surfaces. In addition, in the present case of TbPc 2 the molecules are self-assembled into well-ordered islands leading to highly uniform molecular ensembles with out-of-plane easy axes.…”
Section: Communicationmentioning
confidence: 84%
See 4 more Smart Citations
“…On the contrary, our data on TbPc 2 multilayers on MgO reveal that vertical interactions accelerate magnetization relaxation. [ 20,21 ] In summary, we have demonstrated that MgO thin fi lms realize the combination of effi cient protection from electron scattering and weak molecule-surface hybridization to achieve optimal properties of SMMs on electrode surfaces. In addition, in the present case of TbPc 2 the molecules are self-assembled into well-ordered islands leading to highly uniform molecular ensembles with out-of-plane easy axes.…”
Section: Communicationmentioning
confidence: 84%
“…We use nonmagnetic, insulating MgO, wellknown in inorganic spintronic applications, [ 17,18 ] which allows to control the electron tunneling rate over many orders of magnitude. [ 19 ] Moreover, we employ the TbPc 2 SMM [ 14,15,[20][21][22][23] as a model system. In the neutral molecule, the Tb(III) ion exhibits an electronic spin state of J = 6.…”
mentioning
confidence: 99%
See 3 more Smart Citations